Adsorption Competition between H+ and Cd2+ Ions Toward Active Sites on Ionic Imprinted Mercapto-Silica Hybrid - Buhani, Buhani (EKSAKTA: Journal of Sciences and Data Analysis, 2012)
Adsorption process on Cd2+ionic imprinted mercapto-silica hybrid material (Cd(II)-IIP HMS) has been carried out with studying an adsorption competition between ion H+ and Cd2+ ion upon active sites of Cd(II)-IIP HMS material. Characterization of surface material was based on specific surface area, total volume, and porous diameter. Cd(II)-IIP HMS material with template ionic concentration of each 0.107; 0.214; 0.429; 0.658 mmol g-1 shows that adsorption model is relatively similar, the higher of H+ ion competed, the lower of adsorption capacity of Cd(II)-IIP HMS material upon Cd2+ ion. Keywords: adsorption, active site, mercapto-silica hybrid, ionic imprinted